A Comparison of Daily Versus Weekly Electronic Cigarette Users in Treatment for Substance Abuse. Issue 5 (1st June 2017) - Gubner, Noah R; Pagano, Anna; Tajima, Barbara; Guydish, Joseph
Abstract: Objective: This research examined electronic cigarette (e-cigarette) use by individuals in treatment for substance abuse, a population with a high prevalence of tobacco use and poor smoking cessation outcomes. Methods: We surveyed 1127 individuals from 24 substance abuse treatment centers across the United States. Bivariate analyses and logistic regression were used to examine factors associated with daily ( N = 87) versus weekly ( N = 81) e-cigarette use. Results: Among the full sample, 59.8% reported any lifetime use of e-cigarettes, with 23.6% reporting past 30-day use. Daily e-cigarette users were more likely to have used second-generation, tank-type e-cigarettes, χ 2 (1, N = 165) = 11.54, p = .001, used more flavors overall, t (168) = 2.15, p = .03, and were more likely to report using their e-cigarette continuously throughout the day, χ 2 (4, N = 168) = 16.7, p = .002, compared to weekly e-cigarette users. Over half (57.7%) of the daily and weekly e-cigarette users reported having an e-cigarette device that broke. The logistic regression model adjusting for clinic type and days with poor mental health found that daily e-cigarette users were significantly more likely than weekly e-cigarette users to be from methadone clinics (adjusted odds ratio [AOR] = 2.40, p = .04), and former smokers (AOR = 6.37, p < .002). Conclusions: Daily e-cigarette users in substance abuse treatment were more likely to be from methadone clinics and former cigarette smokers. However, the majority (73.6%) of daily e-cigarette users were current cigarette smokers. E-cigarette device type reliability (eg, breakage) may be an important factor to consider among drug treatment and other populations with lower socioeconomic status. Implications: This study found several differences in the device type, flavors, and use characteristics of daily versus weekly e-cigarette users. While majority of e-cigarette users in substance abuse treatment were current cigarette smokers, daily e-cigarette users were more likely to be former cigarette smokers. Administrators of substance abuse treatment programs should evaluate potential benefits and harms of e-cigarettes when developing program policies.